Influence of Fashion Trends on Social Behavior: An Islamic Educational Perspective Among University Students - Siti Hidayah; Sri Minarti (Al-Qalam Institute, 2025)
This research aims to determine the concept of fashion trends according to the perspective of Islamic education and its implications for the social behavior of students at the Faculty of Islamic University. The background to this research is the development of fashion trends in Indonesia which follows the flow of modernization, which is also felt by Islamic Education students at the faculty. Using qualitative methods with descriptive analysis, data was collected through observation, interviews and documentation, with human instrument techniques for selecting informants. The research results show that the concept of fashion trends from an Islamic education perspective includes an understanding of the intimate parts, fashion models, and the fashion materials used. The implications of this fashion trend for student social behavior include self-awareness, morals, character formation, and personal branding. Motivation for fashion trends from an Islamic education perspective is influenced by the educational environment and self-will based on religious awareness, which has an impact on psychological, sociological and religious aspects.